Analisis Kelayakan Usaha Pembukaan Cabang Baru Pada “UD.Harian” Ditinjau dari Aspek Keuangan - Irawan, Hendri; Febriyanda, Febriyanda; Asneli, Asneli; Sari, Maya Desfita; Khaira, Wilda; Mofa, Wira; Yustiana, Widya (Jurusan PIPS FKIP UMMY Solok, 2020)
Economics condition in Indonesia that more uncertain in business competition are more strict, it made people think to reach profit. The less of job vacancy and the strict in economic, was made many people think to still reach enough income, and also to fulfill their live. One of alternative to solve economic condition that more worst, well by do anymore effort. By made a little venture, middle and big. By still use economic principle that sure can profitable for investor who try to invest their asset in any kind job that their do. UD HARIAN is one of a venture that have activity is locate near Terminal Lama Solok and the owner is Mr. H. Herman who have venture that begin in year 2000. Based on research calculation above can obtain value of NPV is Rp. 115.458.205, PI is 1,7, IRR is 47,1% and Payback Period (PP) during 7 month 1,5 days. Based on the result above can conclude that the plan opened new branch “UD HARIAN” are proper to do. Because time to get back investation during 7 month 1,5 days are more fast than plan to get back investation, and the time is 18 month.